Windows Vista : home entertainment with Windows Media Center and Xbox 360 - Slack, S. E. (Microsoft Press, 2007)
Discover family entertainment choices like never before! This easy-to-use guide features projects for creating the ultimate home entertainment experience for your family. Youll focus on funnot technologyas you discover how to use Windows Vista, Windows Media Center, and Xbox 360. Written by a family for your family, this book highlights the features and capabilities that are most important to you. Its organized by activitysetting up your system, creating digital family memories, and healthy gaming for the entire family. Youre no longer limited to watching a video on your PC, or keeping your music on your MP3 device. Now, you can extend your entertainment possibilities through the entire house for everyone to enjoy!